Miscibility study of gaharu essential oil in water and organic solvents - Latifah, Abu Bakar (2012)
This research is a study about miscibility of gaharu essential oil in water and organic solvents.The scope of this study is to compare polar and non-polar compound which miscible well in gaharu essential oil.Gaharu essential oil is very viscous,smelly,non-sticky and dark-brown oil.This essential oil has a highly market demand because of the value such as it used in incense, perfume and medicine.In this study,the miscibility of gaharu is studied by comparing the chemical components in gaharu essential oil in two different solvent,which is polar and non-polar.Miscibility of gaharu essential oil in water and organic solvents is actually a continuous research work to improve the extraction of gaharu hydro-distillation technique that using water as a solvent and to identify any recovery gaharu maker compound that dissolve in water for each stage of multistage extraction.To perform analysis,FTIR and GCMS are used to determine the chemical compound in gaharu essential oil.The main chemical component in gaharu essential oil is agarospirol, eudesma-4(14),7(11)-diene,α-guaiene,selina-4(15),7(11)-dieneand selinene.But,after gaharu essential oil mixed with water and let for one day,percentage of quality chemical components in gaharu essential oil is reduced.It shows that some of the chemical component tends to dissolve in the water.Furthermore,the smell of water itself just likes gaharu essential oil smell.It coincides with the theory that polar molecule will tend to dissolve anything polar molecule and non-polar molecule will tend to dissolve anything non-polar molecule.